MicroRNA-939 amplifies Staphylococcus aureus-induced matrix metalloproteinase expression in atopic dermatitis - Wang, Jiating; Huang, Yejing; Wu, Xinfeng; Li, Dongqing (Frontiers in Immunology, 2024)
Atopic dermatitis (AD) is a common chronic inflammatory skin diseases that seriously affects life quality of the patients. Staphylococcus aureus (S. aureus) colonization on the skin plays an important role in the pathogenesis of AD; however, the mechanism of how it modulates skin immunity to exacerbate AD remains unclear. MicroRNAs are short non-coding RNAs that act as post-transcriptional regulators of genes. They are involved in the pathogenesis of various inflammatory skin diseases. In this study, we established miRNA expression profiles for keratinocytes stimulated with heat-killed S. aureus (HKSA). We found that miR-939 was highly upregulated in HKSA-stimulated keratinocytes and AD lesions. In vitro studies revealed that miR-939 increased the expression of matrix metalloproteinase genes, including MMP1, MMP3, and MMP9, as well as the cell adhesion molecule ICAM1 in human primary keratinocytes. In vivo studies indicated that miR-939 increased the expression of matrix metalloproteinases to promote the colonization of S. aureus and exacerbated S. aureus-induced AD-like skin inflammation. Taken together, these findings suggest that miR-939 is an important regulator of skin inflammation in AD.